Fibrinolytic Alterations in Sepsis: Biomarkers and Future Treatment Targets - Larsen, Julie Brogaard; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2021)
Sepsis is a life-threatening condition which develops as a dysregulated immune response in the face of infection and which is associated with profound hemostatic disturbances and in the most extreme cases disseminated intravascular coagulation (DIC). In addition, the fibrinolytic system is subject to alterations during infection and sepsis, and impaired fibrinolysis is currently considered a key player in sepsis-related microthrombus formation and DIC. However, we still lack reliable biomarkers to assess fibrinolysis in the clinical setting. Furthermore, drugs targeting the fibrinolytic system have potential value in sepsis patients with severe fibrinolytic disturbances, but these are still being tested in the preclinical stage. The present review provides an overview of key fibrinolytic changes in sepsis, reviews the current literature on potential laboratory markers of altered fibrinolysis in adult sepsis patients, and discusses future perspectives for diagnosis and treatment of fibrinolytic disturbances in sepsis patients.
Keywords: sepsis; coagulation; fibrinolysis; plasminogen; plasmin; plasminogen activator; plasminogen activator inhibitor; thrombin-activatable fibrinolysis inhibitor; antifibrinolytic proteins